Teknik Perbanyakan Amorphphallus titanum Secara Vegetatif Melalui Metode Setek Rachis: Potensi dan Tantangan - Lestari, Dita Indah; Yani, Ariefa Primair; Karyadi, Bhakti; Parlindungan, Deni; Defianti, Aprina (Jurnal Biotek, 2025)
Amorphophallus titanum is an endemic flora of Sumatra that was listed in the IUCN Red List in 2018 under the endangered category. Conservation efforts must be undertaken to preserve A. titanum both ex situ and in situ. Additionally, artificial propagation of plants needs to be carried out to obtain seedlings that can be replanted in their natural habitat or conservation areas. Propagation through the rachis cutting method is interesting to conduct because it is considered easier and more cost-effective compared to other methods. This research aims to determine the potential success of the planting media used and the challenges faced in the propagation of A. titanum through the rachis cutting method, conducted at the Pondok Sains Terpadu (POSTER) conservation, Science Education Study Program, Faculty of Teacher Training and Education, University of Bengkulu. The planting media used were cocopeat and soil, with 40 samples of A. titanum rachis and 20 repetitions for each planting medium. The research results show that the cocopeat medium produced a higher success rate (15%) than the soil medium (0%). Callus appeared in the 8th week, followed by buds in the 12th week. The leaves experienced decay and drying in the 16th week, but the buds continued to grow until they bloomed perfectly in the 20th week. The failure of rachis cutting propagation using average soil media was observed from the 4th week after planting. Thus, it can be concluded that cocopeat media shows potential to support the propagation efforts of A. titanum through the rachis cutting method. The challenges of this research are influenced by pest and disease disturbances (S. rolfsii, Collembola, and H. haydeniana) due to the open research location, as well as environmental factors such as temperature, humidity, light, and pH of the growing medium.